2011
DOI: 10.1007/s00003-011-0704-5
|View full text |Cite
|
Sign up to set email alerts
|

The coenzyme Q10 content of food supplements

Abstract: In the European Union (EU), food supplements are regulated as food and their use is expanding rapidly. There is no enforcement to ensure that good manufacturing practices (GMPs) are followed during production but manufacturers are fully responsible for their products. Recently, the safety and quality of supplements available in the market has come into question. In our surveillance, we examined coenzyme Q10 content of 58 food supplements available in three EU member states or from Internet stores using high-pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 25 publications
0
18
0
1
Order By: Relevance
“…Previous studies have found that declared Se contents in FS from the EU market does not agree with its actual levels with just as little as 20% of investigated products meeting the acceptable margin . Such discrepancies were also reported previously for content of coenzyme Q10 (Pravst and Ž mitek 2011), folic acid, vitamin A, vitamin C (Brandon et al 2014) and vitamin D (Verkaik-Kloosterman et al 2017). As demonstrated by Gabriels and Lambert (2013), the nutritional value of the FS declared on container label is an important factor assisting the consumers' decision-making processes, when purchasing a product.…”
Section: Discussionmentioning
confidence: 72%
“…Previous studies have found that declared Se contents in FS from the EU market does not agree with its actual levels with just as little as 20% of investigated products meeting the acceptable margin . Such discrepancies were also reported previously for content of coenzyme Q10 (Pravst and Ž mitek 2011), folic acid, vitamin A, vitamin C (Brandon et al 2014) and vitamin D (Verkaik-Kloosterman et al 2017). As demonstrated by Gabriels and Lambert (2013), the nutritional value of the FS declared on container label is an important factor assisting the consumers' decision-making processes, when purchasing a product.…”
Section: Discussionmentioning
confidence: 72%
“…This can be explained by the fact that the strongest evidence is available for the beneficial role of CoQ10 supplementation in cardiovascular health but, considering that studies were not performed on healthy population groups, such evidence cannot be used to substantiate health claims for foods . On the market, CoQ10 is mainly used in food supplements , although it can also be found in functional foods. For example, CoQ10 was added as a functional ingredient to 3.5% of yoghurts sold in the Slovenian food supply in 2011 .…”
Section: Introductionmentioning
confidence: 99%
“…In practice, such controls mainly focus on assuring adequate safety by controlling for contaminants and additives (Pravst and Žmitek 2011). Nutritional composition is usually not considered a health risk and is therefore less controlled.…”
Section: Quality Of Functional Foodsmentioning
confidence: 99%
“…probiotics) etc. (Pravst and Žmitek 2011). The appropriate content of these ingredients in final products must be achieved using suitable production standards (including quality control of both raw materials and the final product) and stability during the manufacturing process and shelf life.…”
Section: Quality Of Functional Foodsmentioning
confidence: 99%
See 1 more Smart Citation